Perilaku Menyontek Ditinjau dari Locus of Control pada Pelajar SMA - Desi, Desi; Elvinawanty, Rianda; Marpaung, Winida (Philanthropy: Journal of Psychology, 2018)
Subject of the survey consist of 117 students on Sriwijaya senior high school by total sampling method. The results showed there were significantly relationship locus of contol with cheating. External with correlate coefficient 0.848 and sig. 0.000 (p
Keywords: Cheating; Locus Of Control